The Lack of Authority in Determining State Losses: A Legal Anomaly in Corruption Cases - Nur Fadhilah Mappaselleng; Zul Khaidir Kadir (Widya Pranata Hukum : Jurnal Kajian dan Penelitian Hukum, 2026)
This study analyzes the legal problems of determining state losses in corruption cases in Indonesia, especially regarding the unclear institution that is legally authorized to determine it. This study was conducted using normative research with a statute approach. The results of the study indicate that there is no explicit norm that establishes the Audit Board of Indonesia (BPK) as the sole institution authorized to determine state losses in criminal cases. This opens up space for investigators and prosecutors to use internal estimates or audits from non-constitutional institutions, which raises the potential for excessive criminalization, inter-institutional conflict, and legal uncertainty. This study recommends harmonization of legislation that integrates BPK investigative audits as the main evidence in corruption criminal proceedings and encourages the reconstruction of inter-institutional procedures to ensure the principle of due process and legal justice.